Teaching and learning Law through an active methodology - Soares, Leonardo Ferreira (2022)
Law school presents expectations that it will provide power, social status and financial gain. When faced with legal education in several schools, the student enters the banking education described by Paulo Freire, where the teacher, active subject, deposits in the head of the student, passive subject, the content charged by the menus. In the effort to build knowledge where the student is an active subject of the process as well as to pass on the acquired knowledge, in a constant exchange. Active methodologies in legal education enable students to learn through discoveries, the development of their analytical skills and their motivation. In this article we present three active methodologies: Problem-based learning (PBL), a legal teaching methodology centered on students, enabling them to learn through discoveries, the development of their analytical skills and their motivation. Project-based learning (PBL), combining various teaching strategies (lectures, videos, tests, dynamics, experimentation) based on the results that the teacher wants from the student. The flipped classroom method proposes interaction and debate between students, giving them an active role in learning. In this sense, one of the main pillars is that, when discussing a topic with a colleague, he can learn from the other, promoting conceptual learning through this dialogue. It is necessary to adopt such methods in classes taught in the legal sciences, for the training of critical and reflective professionals, for this to occur, teachers and managers must understand and be open to their use.